Green Synthesis of Selenium Oxide Nanoparticles Using Pleurotus ostreatus (Oyster Mushroom) Preparation Characterization and Antimicrobial Efficacy (Asian Journal of Pharmaceutics (AJP), 2025)
This study aimed to environmentally synthesize selenium oxide nanoparticles (SeO2 NPs) using Pleurotusostreatus (oyster mushroom) extract and evaluated their antimicrobial efficacy against Streptococcus mutansand Enterococcus faecalis. SeO2 NPs were synthesized via an aqueous extract of P. ostreatus and characterizedusing ultraviolet-visible spectroscopy, Fourier transform infrared spectroscopy, and X-ray diffraction (XRD)to determine their optical, functional, and structural properties. The antimicrobial efficacy of the synthesizednanoparticles was assessed against oral pathogens S. mutans and E. faecalis using the agar well diffusion method.Scanning electron microscopy (SEM) was used to analyze SeO2 NPs surface shape and size distribution. SEMscans showed that SeO2 NPs are homogeneous and spherical with an average particle size of up to 10 nm. Well-dispersed particles show less aggregation. The XRD pattern shows no extra peaks, indicating that the synthesizednanoparticles are phase-pure. SeO2 NPs ’ antibacterial activity increases with concentration. Positive control (PC),a traditional antibiotic, has the largest inhibitory zones for both bacteria, proving its efficacy. At a dosage of100μg/mL, SeO2 NPs approach the PC’s efficiency, suggesting potential as an alternative antibacterial agent. SeO2NPs were synthesized utilizing a green method and characterized using XRD and antibacterial tests. The majorfindings reveal that green-chemistry SeO2 NPs are efficient against S. mutans and E. faecalis. Nanoparticles wereeffective at various doses, with the strongest inhibitory zones at higher ones. Green synthesis is necessary to avoiddangerous chemicals and protect the environment.